ANALISA PENGARUH SUBSTITUSI LIMBAH PLASTIK SEBAGAI AGREGAT KASAR TERHADAP KUAT TEKAN BETON - muhamad iqbal saputra; Abdi Nasrullah (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2019)
In general, concrete is composed of cement, fine aggregate, coarse aggregate, water and additional substances if needed. But along with the development of science and technology, concrete constituent materials can also change or be combined with organic or inorganic materials such as plastic waste materials and others. HDPE Plastic (High-Density Polyethylene) Is a type of plastic that is usually used to make milk bottles, detergent bottles, shampoo bottles, moisturizing bottles, oil bottles with code No. 2., toys, and some plastic bags. PET (Polyethylene Terephthalate) PETE or PET is one of the plastics used for food containers, bottles of mineral water and several other wrappers. This plastic is designed for one-time use only. With the use of HDPE and PET plastic waste at a percentage of 20% for concrete compressive strength was not achieved, normal concrete = 15.88 concrete B.HDPE = 12.01, B.PET = 11.71, BC = 12.39 but for concrete weight decreasing, normal concrete = 2330 kg, m3 B.HDPE concrete = 2122 kg, m3, B.PET = 2128 kg, m3, BC = 2096 kg, m3. For the composition of the optimum concrete mixture of the three compositions (B.HDPE, B.PET, BC) obtained the composition of BC which has the most optimum value of 12.39 Mpa, but does not reach the compressive strength of the plan of 15 Mpa.